(untitled) (Architecture Image Studies, 2025)
This study explains the causal mechanism linking Risk Management Practices (RMP) to specific Sustainable Development Goal (SDG) outcomes within higher education. Using PLS-SEM on a survey of 210 Thai administrators, we test a new mediation model. The findings indicate that strategic "drivers" (Risk Governance & Strategy) have no direct impact on sustainability. Instead, their influence is fully mediated by operational "mechanisms" (Risk Performance & Monitoring). These mechanisms are the significant direct predictors for both Operational & Environmental outcomes (related to SDG 7, 9, 11, & 12) and Social & People outcomes (related to SDG 3, 5, & 8). This study provides a new process model, proving that strategy must be translated into operational action to achieve tangible sustainability results.